Number three as a law of science. In praise of number three - Maciuk, Arkadiusz; Smoluk, Antoni (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
Comprehension of nature, in the simplest and quickest fashion, boils down to the differentiation of three states. This is probably related to the psychological fact that the human mind grasps only natural numbers from zero to three and the other numbers it calculates. We live in a divalent world created by Aristotle. However not everything can be reduced to two categories: “yes” and “no”, because Nature is abundant. The principle of continuity which facilitates understanding is in natural conflict with the binary description of the world. Ever since the times of Aristotle it has been normal to use in science a description of the world that is reduced to two states: “true” and “false”. In nature it is more obvious to distinguish three states: low-medium-high or negative-neutral-positive, etc. Man embraces at a single glance sets of three elements at most, and more numerous sets are divided into parts. Binary logic may have a negative impact on the process of teaching and examinations, especially if the tests are used.
Didactics of Mathematics, 2016, No. 13(17), s. 25-35
Keywords: perception of natural numbers; three-valued logic; test exams